Validasi Nilai Simulasi Faktor Keamanan Pada Putaran Kritis Poros ST41 - Anggara, Fajar (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2020)
A Shaft has been widely used in machinery construction, transmitting power from one component to another. Firstly, the shaft must be calculated for its safety factor before being used for the actual application. In this study, the specimen used for testing was ST 41 material. The safety factor is essential for engineering design, used to evaluate that machine elements' system is guaranteed safety with minimal dimensions. The way to nd the safety factor of this test tool is to use actual calculations and simulations on the Solidworks software. The value of the safety factor obtained from the calculation will be compared with SolidWorks software's simulation results. The results obtained in a calculation analysis for the actual stress of 6,65x106 N/m2 and the safety factor of 55, while for the actual stress (von Mises) in a simulation of 6,8x106 N/m2 and its safety factor of 54. After validating the data, there is a difference of 1.1% for the actual stress and 0.9% for the value of its safety factor.